ZIF-8/PLA porous composite microspheres: preparation, characterization, and effective removal of gaseous benzene - Li, Jiali; Sun, Peijian; Wang, Yipeng; Sun, Xuehui; Peng, Bin; Xu, Weili; Liu, Mengmeng; Nie, Cong (Frontiers in Materials, 2025)
Benzene is a prevalent environmental contaminant, and its effective removal through adsorption is crucial to mitigate both environmental and health impacts. In this study, a series of zeolitic imidazolate framework-8/polylactic acid (ZIF-8/PLA) porous microspheres were prepared to adsorb/remove gaseous benzene. The ZIF-8/PLA microspheres were prepared via the double emulsion-solvent evaporation method with ammonium bicarbonate as the foaming agent, and the structures were well adjusted by varying the fabrication parameters of the microspheres. The adsorption of gaseous benzene by these microspheres was evaluated both in flowing benzene vapor and in cigarette smoke. These ZIF-8/PLA microspheres exhibited an interconnected porous network structure with a high surface area, which is beneficial for the fast gas diffusion and effective adsorption, particularly suitable for complex environments with high gas flow rates. The adsorption capacity of gaseous benzene on these ZIF-8/PLA microspheres is as high as 77–238 mg/g and 18%–44% of benzene can be removed from the cigarette smoke by using these ZIF-8/PLA microspheres as absorbents due to the interconnected hierarchical porous network enhancing the fast gas diffusion and the strong π-π stacking interactions of ZIF-8 towards aromatic hydrocarbons, showing the great potential of these ZIF-8/PLA microspheres as adsorbents for efficient removal of gaseous benzene.